THE FUNCTION OF MEUNASAH IN SOCIAL CULTURAL COMMUNICATION PROCESS WITHIN ACEHNESS SOCIETY - Wahid, Umaimah (Journal of Human Capital Development (JHCD), 2013)
This paper is trying to explain the social communication in the development of Aceh society in which in this development process Meunasah, as in Acehnese civilization, is a community center. In this respect, Meunasah exercises significant role as a learning centre in the process of social ultural reconstruction to Acehnese. This means that all empowerment and development process of Acehnese is held in Meunasah, through which the social changes for the social cultural endurances of Acehnese can be examined. Through constructivism paradigm, this writing attempts to find the meaning of and to understand human communication performances. This meaning is specific in nature and is an entity of Acehnese cultural characteristic as social reality And thus, Meunasah, as a cultural institution, has a symbolic power socially culturally, economically and politically. Through this work, it is attempted to be able to find the crucial role and the function of Meunasah in reconstructing Aceh society. Meunasah, in which all the process of social cultural and religion, even, politics are undertaken, is an Acehnese entity. This writing attempts to elaborate the role of Meunasah in conducting the process of social communication, social development as social and cultural symbol of Acehnese civilization, as well as the centre that generates social cultural, economical, and political endurances. From this point, it is impossible to separate the changes that occurred within Aceh society as well as its civilization from Meunasah. The process of the socialization concerned with the strategy in introducing programs or communication plans among the group members in the effort of constructing changes is using communication process in which in doing so it could possibly renders social interactions among society. In this process, the role of communication is perceived capable to establish the social interaction become significantly meaningful and makes possible to the social process within social structure. The social process involves communication interactivity that could create values, norms, social system, a new social process and makes possible to the emergence of social changes in the sphere of social communication development as well. As the entity of the Civilization of Acehnese, Meunasah apparently has power to generate social communication process in the development of Aceh society for centuries. Keywords: social cultural communication, meunasah, social changes